Memorandum re Shortage of Nurses - Labour Party (Great Britain). National Executive Committee ; Labour Party (Great Britain). Advisory Committee on Public Health ; Joint Research Dept. of the Trades Union Congress and the Labour Party; MacCallum, Maude
1924-07 1924 1920s 8 pages Private & Confidential GENERAL COUNCIL TRADES UNION CONGRESS. July, 1924. No. 92 EXECUTIVE COMMITTEE LABOUR PARTY. JOINT RESEARCH & INFORMATION DEPARTMENT. ADVISORY COMMITTEE ON PUBLIC HEALTH. MEMORANDUM RE SHORTAGE OF NURSES. by Miss Maude MacCallum. In the opinion of the Professional Union of Trained Nurses, the three main causes for the shortage of probationers, (outside the fact that nearly all professions and trades are now open to women), are as follows:- 1. The attitude of Hospital Authorities towards the Working Nurse; 2. The attitude of the Medical Profession towards Nurses; b, The scarcity of good appointments after they are trained, 1. Attitude of Hospital Authorities towards the Working Nurse. (A) (i) A probationer does not enter hospital as a student, to be given the best teaching possible with regard to her profession, but as a necessary employee to carry on the work of the Institution. On entering she is expected to sign an agreement of service for three or four years, and although certain penalties are attached in many instances if she breaks her engagement, it is often specifically stated that she may be dismissed at a moment's notice by the matron or medical superintendent. We cannot find that any other trade or profession requires indentured or articled pupils to submit to a like treatment. (ii) Many Hospitals, not satisfied with the hard work 292/842/1/14